2021
DOI: 10.1080/21655979.2021.2017578
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of long non-coding RNA associated ceRNAs in intrauterine adhesion

Abstract: Intrauterine adhesion (IUA) is an endometrial fibrotic disease with unclear pathogenesis. Increasing evidence suggested the important role of competitive endogenous RNA (ceRNA) in diseases. This study aimed to identify and verify the key long non-coding RNA (lncRNA) associated-ceRNAs in IUA. The lncRNA/mRNA expression file was obtained by transcriptome sequencing of IUA and normal samples. The microRNAs expression date was downloaded from the Gene Expression Omnibus database. Differential expressions of mRNAs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…A recent study established a complete lncRNA–miRNA–mRNA network in IUA based on ceRNA theory ( Zhang et al, 2022a ). This study identified 418 differentially expressed lncRNAs and 915 differentially expressed miRNAs.…”
Section: Role Of Ncrnas In the Pathophysiology Of Intrauterine Adhesionmentioning
confidence: 99%
“…A recent study established a complete lncRNA–miRNA–mRNA network in IUA based on ceRNA theory ( Zhang et al, 2022a ). This study identified 418 differentially expressed lncRNAs and 915 differentially expressed miRNAs.…”
Section: Role Of Ncrnas In the Pathophysiology Of Intrauterine Adhesionmentioning
confidence: 99%